Answer:
B) x = -7
Step-by-step explanation:
Given equation: [tex]10(x+10)-4=11-5(2x+11)[/tex]
Step 1: Distribute [tex]10[/tex] and [tex]-5[/tex] through the parentheses.
[tex]\implies 10(x)+10(10)-4=11-5(2x)-5(11)[/tex]
[tex]\implies 10x+100-4=11-10x-55[/tex]
Step 2: Simplify (combine like terms).
[tex]\implies 10x+100-4=11-10x-55[/tex]
[tex]\implies 10x+96=-44-10x[/tex]
Step 3: Add [tex]10x[/tex] to both sides.
[tex]\implies 10x+10x+96=-44-10x+10x[/tex]
[tex]\implies 20x+96=-44[/tex]
Step 4: Subtract [tex]96[/tex] from both sides.
[tex]\implies 20x+96-96=-44-96[/tex]
[tex]\implies 20x=-140[/tex]
Step 5: Divide both sides by [tex]20[/tex] to isolate [tex]x[/tex].
[tex]\implies \dfrac{20x}{20}=\dfrac{-140}{20}[/tex]
[tex]\implies \boxed{x=-7}[/tex]